“PENGARUH LATIHAN DRIBBLE SLALOM TERHADAP KETERAMPILAN DRIBBLING PEMAIN SSB BINA BAKAT U-12 PEKANBARU” - Ramayuliardi Ramayuliardi; Slamet Slamet; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstark:. The problem in this study is that there is still a lack of control ofdribbling, so that when the athlete's playing is very slow to dribble. The aim of the studywas to determine the effect of slalom dribble training on the dribbling skills of SSB U-12 Talent Players in Pekanbaru. The form of this study was a weak experiment using adesign of a one-group pre-post test design study, with a population of all Pekanbaru U-12 Talent SSB players as many as 14 people, 14 samples being studied. The instrumentused in this study used a dribble test. The data were then processed with statistics to testthe normality using the lilifours test at a significant level of 0.05α. The proposedhypothesis is that there is an effect of slalom dribble training on the dribbling skills ofSSB U-12 Talent Players in Pekanbaru. Based on the normal test analysis, data Xproduces Lcount of 0.1193 and Ltable of 0.227, which means Lcount <Ltable. while theY variable produces Lcount of 0.1927 and Ltable of 0.227. This means Lcount <LTable.Based on statistical data analysis, there is an average of variables X 15.61 and theaverage variable Y is 1.771, so the data is normally distributed. For example, there isthe effect of slalom dribble training on the dribbling skills of SSB players in PekanbaruU-12 Talent.Key Words: Drible Slalom Exercise, Dribbling Skills